Analysis of the People's Rubber Marketing System in Mandailing Natal: Review of Distribution Channels, Margins, and Efficiency - Muhammad Iqbal; Mitra Musika Lubis (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Smallholder rubber is a leading commodity that plays a vital role in the regional economy, particularly in Mandailing Natal Regency, which is known as one of the main rubber-producing areas in North Sumatra. However, the marketing system for smallholder rubber in this region still faces several structural constraints that significantly affect farmers' income. This article aims to analyze the distribution channels, margin distribution, and marketing efficiency of smallholder rubber in Mandailing Natal using a literature review approach. The data were obtained from various scientific publications, government reports, and agribusiness studies published over the past ten years. The review found two common marketing channel patterns: a long channel (farmers ? local collectors ? wholesalers ? factories) and a short channel (farmers ? wholesalers ? factories). The short channel proves to be more profitable for farmers by reducing intermediaries and increasing marketing efficiency. Additionally, farmers' share of profit margins increases significantly under the short channel. Nonetheless, challenges such as weak farmer institutions, limited market access, and lack of price information remain major obstacles. Therefore, recommended strategies include establishing marketing cooperatives, improving distribution infrastructure, and digitizing price information systems. Enhancing the existing marketing system is expected to improve the welfare of smallholder rubber farmers in Mandailing Natal sustainably.